“When you get the HPV vaccine, it will prevent cervical cancer; it will act as a shield”: adolescent girls’ knowledge and perceptions regarding the human papillomavirus vaccine in Zambia - Lubeya, Mwansa Ketty; Chibwesha, Carla J.; Mwanahamuntu, Mulindi; Mukosha, Moses; Frank, Simone; Kawonga, Mary (Frontiers in Health Services, 2023)
Introduction The human papillomavirus (HPV) vaccination is an important preventive measure for HPV-related conditions such as cervical cancer. In 2019, Zambia introduced a free national HPV vaccination program for 14-year-old girls. However, the adolescents’ knowledge and perceptions regarding the HPV vaccine are not well understood. Therefore, this study aimed to understand adolescent girls’ knowledge and perceptions regarding the HPV vaccine and discuss its acceptability and uptake implications. Methods We conducted a qualitative study in the Lusaka district between June 2021 and November 2021 using semi-structured interviews with adolescent girls aged 15–18 years regardless of their HPV vaccination status. Interviews were transcribed verbatim, and NVIVO 12 was used for data management and analysis. We coded transcripts deductively and inductively based on emerging themes. Perceptions were coded using the health belief model constructs. Results We interviewed 30 adolescent girls to reach saturation. Seventeen girls reported having received at least one dose of the HPV vaccine. Participants expressed variable knowledge and awareness about HPV and the HPV vaccine. Participants exhibited positive attitudes towards the HPV vaccine and perceived it as beneficial. However, there were multiple perceived barriers to vaccination, such as the need for parental consent, not being in school, concerns about vaccine side effects, and belief in myths and misinformation Conclusion The adolescent girls in this study showed variable knowledge and positive attitudes toward the HPV vaccine despite the many perceived barriers. To support increased HPV vaccine acceptability and uptake among adolescent girls in Zambia, it is critical to actively engage stakeholders involved in HPV vaccination, such as adolescents and their parents, and debunk myths and misconceptions about HPV vaccination. Health education in schools and communities should be implemented to increase knowledge about HPV and HPV vaccination among adolescents and their parents.